2016
DOI: 10.20960/nh.583
|View full text |Cite
|
Sign up to set email alerts
|

Ingesta dietética y adherencia a la dieta mediterránea en un grupo de estudiantes universitarios en función de la práctica deportiva

Abstract: Ingesta dietética y adherencia a la dieta mediterránea en un grupo de estudiantes universitarios en función de la práctica deportiva AbstractIntroduction: University students eating habits are moving away increasingly from the Mediterranean Diet (MD) Both nutrition and physical activity are essential to preserve an appropriate health. Objective: To compare food intake between athletes and sedentary University students. Subjects and methods: Cross-sectional study conducted on 49 students from the University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
3
9
0
6
Order By: Relevance
“…Comparing our results with those of other available studies, the Spanish squash players reported a consumption of foods of higher protein content that seems lower in comparison to the dietary patterns observed among adolescent badminton players, who consumed 2-3 daily servings of meat and eggs (da Silva et al, 2007). However, they would partially coincide with the findings of the study of university badminton and basketball players by Redondo et al, who reported a reduced consumption of fish, but an excess intake of meat (Redondo del Río, 2016). Although the caloric percentage and ingested amount of proteins in the diets of our sample are not available, the studies carried out in other racquet sports found that protein consumption provided more than 15% of the total caloric intake (Juzwiak, Amancio, Vitalle, Pinheiro, &Szejnfeld, 2008;Ramires et al, 2012;Vitasovic et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Comparing our results with those of other available studies, the Spanish squash players reported a consumption of foods of higher protein content that seems lower in comparison to the dietary patterns observed among adolescent badminton players, who consumed 2-3 daily servings of meat and eggs (da Silva et al, 2007). However, they would partially coincide with the findings of the study of university badminton and basketball players by Redondo et al, who reported a reduced consumption of fish, but an excess intake of meat (Redondo del Río, 2016). Although the caloric percentage and ingested amount of proteins in the diets of our sample are not available, the studies carried out in other racquet sports found that protein consumption provided more than 15% of the total caloric intake (Juzwiak, Amancio, Vitalle, Pinheiro, &Szejnfeld, 2008;Ramires et al, 2012;Vitasovic et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…The international players had a greater consumption of nuts (5 or 6 times per week) than the national level players (twice a week). For comparative purposes, the only study focused on racquet sports in which the consumption of nuts was analyzed was that of Redondo et al (Redondo del Río, 2016), who reported a consumption of less than 2 servings per week, similar to that of our national players. A study of elite canoeists found that one in three did not usually eat nuts (Alacid et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…Students with low adherence to the MD tended also to not engage in physical activity, whilst those typically adhering to a MD diet also show higher levels of physical activity [50,51,52]. One potential explanation for this is that young people who practice physical activity tend to consume a nutritious diet to obtain greater results in terms of performance, body image, or wellbeing [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to maximize the appropriateness and/or utility of the instruments used, whether quantitative or qualitative, the aim of this work is to describe the process of building and optimizing the development of a qualitative instrument, which will enable to integrate qualitative records with a quantitative analysis. Thus, this work developed a new observation instrument from a mixed method perspective to analyze the offensive collective performance and the tactical characteristics of the action of collective offensive game in soccer, considering the behavior of the opponent team and also contextual dimensions, it also verified the reliability of such instrument, bearing in mind that this methodology is ideal for research on behaviors that occur in soccer (Anguera and Hernández-Mendo, 2013, 2014).…”
Section: Introductionmentioning
confidence: 88%